Ethnographic discourse and indigenous representation in the work of Ignacio Domeyko: a dissident voice - Gallardo, Viviana (Revista Chilena de Antropología, 2019)
Ignacio Domeyko's speech on Araucanía enunciated in the mid-19th century is addressed. It is sought to determine if this discourse, prepared according to the method of the naturalists, contributed to building a new representation on the indigenous world in Chile. It is argued that in Domeyko a new way of referring to the indigenous world was created, backed by first-hand knowledge and recognition of the “Indian” of the present. A discourse analysis is made of the texts written by the naturalist about his trip to Araucanía in 1845, concluding that his work contributes to questioning the imaginary about the indigenous people who hegemonized the national construction process in Chile.